Takayasu’s Arteritis: Rare Cause of Hypertension in Children - Lamichhane, Reshma Dhakal; Chapagain, Ram Hari (Journal of Nepal Paediatric Society, 2019)
Takayasu arteritis (TA) is a large vessel vasculitis that involves the aorta, its major branches and pulmonary arteries. Diagnosis of TA during childhood remains challenging due to the non-specific symptoms. We report a six years age boy with unresolved hypertension who was later diagnosed as childhood TA. Oral corticosteroid was started 2mg/kg/day. TA is rare in children; Childhood TA must be considered in children who present with, hypertension and increased acute phase reactants.